Chronic endometritis in In-Vitro fertilization failure patients - Afaf T Elnashar; Mohamed Sabry (Global Journal of Fertility and Research - Peertechz Publications, 2021)
Introduction: Chronic Endometritis (CE) is a common cause of infertility in asymptomatic patients and its diagnosis and treatments improved assisted reproduction technique outcome in most of the specialized centers. Diagnosis of CE in endometrial biopsy by Hematoxylin and Eosin (H&E) stain is hard to identify chronic inflammatory cells from the stroma and the use of plasma cells-specific stains is helpful.  Aim of the work: Evaluation of the use of CD138 in the identification of plasma cells in endometrial biopsy of patients with previous IVF trial failure.  Material and methods: Hysteroscopic and curettage endometrial biopsies from fifty-five females with previous IVF trial failure were stained with H&E and CD138 immunostaining for detection of plasma cells.  Results: Plasma cells were identified in 52.7% of cases by H&E and in 6/55 by CD138 immunostaining. CD138 is more sensitive in detecting plasma cells in endometrial biopsy than H&E stain. There was a significant statistical correlation between CE and abnormal uterine bleeding, abortion and primary infertility (P> 0.5).  Conclusions: Diagnosis of CE is helpful in infertility patients with IVF trial failure to improve the outcome of the maneuver. CD138 is more sensitive for plasma cells especially in endometrial biopsies than H&E.